Component composition of the structure of proffesional image of futare masters of industrial training of construction profile - Volosyuk, T. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Professional education acquires qualitative changes for the production of claiming specialist of new quality level, who is able to quick adaptation according to the rates of scientifictechnological development of society. The scientific-technological progress provides the quick development of production that stipulates the necessity in specialists of professional-technical specialties, in general and in construction profile particularly. The attention is raised mostly to personal, behavioral components of professional level of master of industrial braining of construction profile and the peculiarities of its image formation. Purpose. The analysis of image of future masters of industrial training of construction profile and the allocation of the components of its structure. Results. Specific character of professional activity of master of industrial training of building construction is rather complex through is causes the existence of professional production competence, organizational and management skills and weighty teaching skills. That is why we understand the image of the future master of industrial training of construction profile as cumulative image of the specialist, who combines and synchronizes personal professional characteristics in complex way. There determined the personal-intellectual, practically-effective and social-image components of professional image of future industrial training masters of construction profile. The effectiveness of which is caused by the interaction and complementarity to the another for the formation of harmonious image of the professional. Originality. For the first time there analyzed the structure of professional image of future masters of industrial training of construction profile. There also distinguisher its component structure. The scientific conception about the specific character and the structure of the process of formation of the professional image of the notion “the image of the master of industrial training” are the future trends of our research. Conclusion. At the modern period the profession of industrial training of construction profile is updated connection with the lack of provision of professional technical personal. The formation of professional image of the master of industrial training of construction profile as cumulative multy-aspects image, reflected in social expectations of society, gets exceptional meaning. While organizing the process of formation of professional image of master of industrial training of construction profile it is necessary to take into consideration the component composition of its structure especially personally-intellectual component, practically-effective component and social-image. The outlined components cannot exist isolated with one another. They interact synergistic and amplify each other.